Statistical Analysis Of Results On Miners’ Exposure - J. Brenot; J. W. Piechowski; M. Tirmarche (Society for Mining, Metallurgy & Exploration, 1981)
INTRODUCTION Statistical analysis of results obtained by workers survey is very often limited to the determination of the collective dose and mean annual values. This information is not sufficent by itself for radiation protection purposes since the cumulative exposure of a worker during his working life is not taken into account. A more complete analysis would be obtained by considering both: [ ] These two notions are different. The former depends on the evolution of the protection with time and is related to annual limits (ICRP, 1977 and ICRP,1977 a). The second depends mainly on the works performed during the period of survey, the interference of protection evolution is weakened. So it is useful to foresee how the individual average annual doses would be when considering survey periods of 5, 10 years, or more. STUDIED POPULATION In order to analyse the two previously mentionned notions it is necessary to follow up a well defined population of workers which is continuously exposed to the radiological hazards on a long enough period. The selected population is that of the workers of the French uranium mines always present during the 1971-1979 period (9 years). The number of individuals is 937. The radiological hazards are: 1. exposure to radon and short-lived daughters 2. exposure to long-lived ore dust 3. external irradiation. The workers of the uranium mines are exposed to these radiological risks in different ways according to the work performed. It is therefore necessary to subdivide the population into more homogeneous groups with respect to the radiological risks. Three groups are considered: - Group 1 : 227 individuals whose radon and dust exposures are always nil - Group 2 : 449 individuals whose radon and (or) dust exposures are different from 0 every year - Group 3 : 261 individuals represent a mixed category. Some features of these groups are given in table 1. [ ] The 937 followed individuals represent approximatively the half of the whole population of the French uranium mines. Taking into account the procedure adopted to select the studied population, it appears clearly that this population is not representative of the whole miner population. DOSIMETRIC RECORDS Three risk indicators are considered .Individual annual exposures to radon and its shortlived daughters. They are determined by ambient monitoring based on radon concentration measurements and recording of the times elapsed in the various workplaces. For each worker the annual exposure is represented by the mean annual air concentration and is expressed as a fraction of the maximum annual concentration (MAC). Given the administrative arrangements and the effective state of equilibrium between radon and its daughters, the maximum annual concentration is practically equivalent to 1 Working Level = 2.08 x 10- 5 jm-3. (UNSCEAR, 1977). . Individual annual exposures to long-lived ore dust which are also expressed in fraction of the maximum annual concentration. . Individual annual doses of external irradiation (X and [y] rays) expressed in mSv (= 10-3 Sievert). Irradiation monitoring is based on use of individual film badges.